Flavonoid Synthesis and Metabolism During the Fruit Development in Hickory (Carya cathayensis) - Chen, Jia-Hui; Hou, Na; Xv, Xv; Zhang, Da; Fan, Tong-Qiang; Zhang, Qi-Xiang; Huang, You-Jun (Frontiers in Plant Science, 2022)
Hickory (Carya cathayensis) kernel is rich in powerful bioactive flavonoids, which can remove excess free radicals in human body and play an important role in regulating the physiological metabolism of the plant. In this study, the changes of flavonoids in hickory exocarp and embryo during development were investigated. In this study, 72 DEGs involved in the regulation of flavonoid biosynthesis in fruits were identified, and TT4, CCoAOMT1, UGT71D1, C4H, F3H, TT8, FLS1 and LDOX were identified as the core genes of flavonoid biosynthesis. A total of 144 flavonoid related metabolites were detected by metabolite analysis. Transcriptome and metabolome analysis combined to construct the flavonoid biosynthesis regulatory pathway in the development stage of hickory fruit. Our results provide a theoretical basis for the exploration and regulation of functional genes related to flavonoid biosynthesis and metabolism in hickory and other plants and the breeding of new varieties of walnut.